Long-term outcomes of PD-1 inhibitors plus chemotherapy as first-line treatment for advanced HER2-negative gastric cancer: an updated systematic review and meta-analysis - Tong, Juping; Zhou, Shanmei; Yin, Shan; Wang, Xiaojian; Liang, Xinyi; Quan, Jieru; Zhang, Duo; Wu, Shanguang; Wei, Yilun (Frontiers in Immunology, 2025)
IntroductionThis meta-analysis was designed to compare the long-term outcomes of first-line programmed cell death protein 1 (PD-1) inhibitors plus chemotherapy versus chemotherapy in patients with advanced HER2-negative gastric cancer (GC).Materials and methodsFour databases (PubMed, Embase, Web of Science, and the Cochrane Library) were searched for randomized controlled trials (RCTs) comparing first-line PD-1 inhibitors plus chemotherapy to chemotherapy in patients with advanced HER2-negative GC. The search was conducted from the databases establishment to October 11, 2025. Overall survival (OS), progression-free survival (PFS), objective response rate (ORR), treatment-related adverse events (TRAEs), and Grade≥3 TRAEs were subjected to meta-analyses.ResultsSix RCTs were included in the meta-analysis. The meta-analysis included a group of 6038 patients diagnosed with untreated advanced HER2-negative GC. Within this cohort, 3026 patients were administered first-line PD-1 inhibitors together with chemotherapy, while 3012 patients received first-line chemotherapy alone. Compared with chemotherapy, first-line PD-1 inhibitors plus chemotherapy yielded superior OS (HR = 0.91; 95% CI 0.89 to 0.93; P<0.01), PFS (HR = 0.89, 95%CI 0.87 to 0.91 P<0.01), and ORR (RR = 1.22, 95% CI, 1.16 to 1.29, P<0.01). With regards to safety, first-line PD-1 inhibitors plus chemotherapy exhibited a greater likelihood of encountering TRAEs (RR = 1.02, 95% CI: 1.00 to 1.04, P = 0.03) and Grade≥3 TRAEs (RR = 1.16, 95% Cl: 1.08 to 1.25, P<0.01) in comparison to chemotherapy.ConclusionsCompared with chemotherapy alone, PD-1 inhibitors plus chemotherapy as first-line therapy provided improved OS, PFS, and ORR. Furthermore, the heightened efficacy of PD-1 inhibitors plus chemotherapy was accompanied by a rise in TRAEs and Grade≥3 TRAEs.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251015248.